Faktor- Faktor yang Mempengaruhi Kinerja Keuangan Pemerintah Daerah dengan Belanja Modal Sebagai Variabel Intervening - Mukhibad, Hasan; Aji, Mugi Wismoyo (Unand Press, 2020)
The purpose of this study is to determine whether there is an influence of local own-source revenue (PAD), regional loans, and intergovernmental revenue on the financial performance of local governments and their influence if mediated by capital expenditure. The population in this study is the Regency / City Governments in Central Java consisting of 29 Regencies and 6 Cities in 2014-2016. This study uses secondary data in the form of a report on the realization of the Central Java Regional Government Budget in 2014-2016. Hypothesis testing in this study uses path analysis with two regression models. The results of the research for the first regression model show that regional original income and the Intergovernmental Revenue have a significant effect on capital expenditure. The Regional Loan variable has no significant effect on capital expenditure. For the second regression model of regional own-source revenue and the Intergovernmental Revenue does not have a significant effect on financial performance, the regional loan variable has a significant effect on the financial performance of regional governments. Variable of local original income, regional loans, and intergovernmental revenue have no significant effect on the financial performance of local governments through capital expenditure. Intervening variables are not proven to be able to mediate the effect of independent variables on the dependent.